Dinamika Seni Lukis Wayang Kaca Desa Nagasepaha Kabupaten Buleleng - Paramita, Ida Bagus Gede (Humanis; Vol 26 No 4 (2022), 2022)
Research on the Nagasepaha Glass Puppet Painting, hereinafter abbreviated as SLWKN, uses discourse analysis of socio-cultural change in SLWKN. The approach used is a qualitative approach. Collecting data using interviews, documentation and literature study. The method of analysis, carried out in a descriptive-qualitative way by using the working stages of the theory of socio-cultural change. The results of the analysis are presented in a systematic and structured manner. The results of this study provide an answer that the dynamics of the existence of SLWKN continue to change in order to ensure the survival of this painting as well as to guarantee the economic resources of the art community in Nagasepaha Village